Existence of Standing Waves for a Generalized Davey-Stewartson System - Xiaoxiao Hu; Xiao-xun Zhou; Wu Tunhua; Min-Bo Yang (Abstract and Applied Analysis)
The purpose of this paper is to investigate the existence of standing waves for a generalized Davey-Stewartson system. By reducing the system to a single Schrödinger equation problem, we are able to establish some existence results for the system by variational methods.